Degree of Public School Practice Total Quality Standards Central Gaza Strip, and Relationship to Educational Strategic Planning Effectiveness from Teachers' View - Mezyed, Sabreen Salman; Al Muzayn, Suleiman Hussain (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the degree to which government schools in Al Westa governorate of Gaza Strip for Palestine, their role in applying the Total Quality Management standards on the effectiveness of educational strategic planning from the point of view of teachers, and used the analytical description approach, and prepared the questionnaire, which consisted of (50) paragraphs, the study sample was selected by the simple random method, which consisted of (303) male and female teachers from population of the study, consisted of (1435) from government schools teachers in Al-Westa governorate of Gaza Strip for Palestine, and the results of the study showed that the degree to which government schools their role in applying the Total Quality Management standards is high with a percentage of (73.98%),and the degree of the effectiveness of educational strategic planning is high with a percentage of (75.42%), and there is a direct positive correlation between the mean scores of the sample members of the study for and the degree to which government schools their role in applying the Total Quality Management standards and the degree of the effectiveness of educational strategic planning from the point of view of teachers. And in light of the results of the study, the researchers recommend reciprocal visits between government schools to exchange ideas and proposals in the field of applying Total Quality Management standards, and conducting more similar studies in the rest of governorates of the Gaza Strip that are not included in the community, and it's comparison with the results of the current study has reached.
Keywords: Total Quality Management standards; strategic planning effectiveness; government schools